PENINGKATKAN KESEJAHTERAAN MASYARAKAT MELALUI PEMAHAMAN PEMASARAN DIGITAL DAN LITERASI KEUANGAN BAGI PELAKU USAHA PEREMPUAN DI DESA SUKAMUKTI - Hilmiana, Hilmiana; Kirana, Desty Hapsari (Batara Wisnu : Indonesian Journal of Community Services, 2023)
Women have an important role in family welfare. Not only being housewives, women are often the backbone of the family economy. However, there is often a lack of knowledge related to managing family finances, which in the end the family’s economic health becomes lame. The purpose of this PPM activity is to provide assistance and training for community in Desa Sukamukti, especially for women entrepreneurs in order to improve family welfare by maximizing their role as women. The activities carried out are related to financial literacy which is focused on managing family finances and also utilizing digital marketing to increase sales and income to support the family economy